Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1136/bjsports-2013-093201
|View full text |Cite
|
Sign up to set email alerts
|

Genes encoding proteoglycans are associated with the risk of anterior cruciate ligament ruptures

Abstract: These independent associations and haplotype analyses suggest that regions within ACAN, BGN, DCN and a region spanning LUM-DCN are associated with ACL injury susceptibility. Taking into account the functions of these genes, it is reasonable to propose that genetic sequence variability within the genes encoding proteoglycans may potentially modulate the ligament fibril properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 59 publications
2
69
1
Order By: Relevance
“…Functional annotation clustering using DAVID revealed significant enrichment of a cluster of 24 genes encoding carbohydrate binding proteins ( P <1.84E-07, P corr = 1.21E-04) that includes aggrecan ( ACAN ), a large structural protein that stabilizes the collagen network in ligament matrix [48]. The majority of these proteins are c-type lectin receptors (CLRs).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional annotation clustering using DAVID revealed significant enrichment of a cluster of 24 genes encoding carbohydrate binding proteins ( P <1.84E-07, P corr = 1.21E-04) that includes aggrecan ( ACAN ), a large structural protein that stabilizes the collagen network in ligament matrix [48]. The majority of these proteins are c-type lectin receptors (CLRs).…”
Section: Resultsmentioning
confidence: 99%
“…Equine degenerative suspensory ligament desmitis (DSLD), a debilitating disorder of horses that leads to collagen disruption and eventual rupture of the suspensory ligament, is associated with a 15-fold increase in aggrecan content of affected ligaments [64]. Moreover, recent work has linked human ACAN rs1516797 with the risk of ACL injury in both males and females [48]. A separate study revealed ACAN gene expression is up-regulated in ACL samples from female compared to male patients that have undergone ACL repair surgery, suggesting a possible etiology for the observed sex differences among patients with ACL injury [65].…”
Section: Discussionmentioning
confidence: 99%
“…Since the previous ACL retreat, a growing number of common DNA sequence variants within genes involved in various biological processes have been associated with susceptibility to ACL rupture. These include variants within several genes that encode collagens [169][170][171][172][173][174][175] and proteoglycans 176 involved in the formation of the collagen fibril, the basic building block of ligaments. A subset of these variants has been specifically associated with ACL ruptures in females but not in males.…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…The genes encoding the proteoglycans aggrecan and decorin 27 were associated with ACL injury. Nonetheless, genes involved in the angiogenesis-associated signalling pathway28 also had its relationship to ACL injury described in the literature.…”
Section: Introduction and Basic Sciencementioning
confidence: 99%